Direct Ophthalmoscopy Toward the Retinal Periphery - Williams, T David; Bader, Dennis A (Canadian Journal of Optometry, 1980)
Direct ophthalmoscopic examination toward the retinal periphery requires the use of increasing amounts of plus lens power in the instrument. The purpose of this clinical study was to determine the amount of additional plus power required to focus on peripheral fundus details.